Pemanfaatan Saccharomyces cereviceae dan Limbah Buah Nanas Pasar Beringharjo Yogyakarta untuk Pembuatan Bioetanol - Sri Ayu Wahyuni; Abdul Hadi Kadarusno; Bambang Suwerda (Poltekkes Kemenkes Yogyakarta, 2016)
One of the organic waste generated from markets is pineapple waste. Parts of pineapple thatcan be eaten is only 53 % while the remaining 47 % were dumped as waste. The peels of pineapple contain 13,65 % sugar, so that can be processed as bioethanol, i.e. ethanol made frombiomass containing cellulose or starch component. The preliminary trial found that the fermentation of pineapple waste in four days with four weight variations of Saccharomyces cereviceaeobtained the highest level of bioethanol at 27,7289 %, i.e. produced from 15 gram of that yeastThe purpose of this research was to know the influence of Saccharomyces cereviceae weightvariation (0 %, 20 %, 40 % and 60 %) and fermentation time variation (4 days, 7 days and 10days) toward the levels of bioethanol produced from pineapple waste of Beringharjo Market, byconducting a post-test only with control group designed experiment. The results show that thehighest levels of bioethanol produced was 40,45354 %, i.e. from the use of 60 % weight of Saccharomyces cereviceae and 10 days fermentation. However, the statistical analysis with two-wayanova test at 95 % level of confidence yielded a probability value >0,05 which means that thelevels of bioethanol produced from those yeast weight variation and fermentation time variationare not significantly different.